Proses Pendidikan Bagi Anak Suku Bajo di Desa Tinakin Laut Kecamatan Banggai Kabupaten Banggai Laut - Hatu, Dewinta Rizky R.; Hatu, Rauf A.; Rahmatiah, Rahmatia (Dynamics of Rural Society Journal, 2024)
Education is one of the crucial aspects for broadening the knowledge of the nation's future generations. A similar situation is observed among the children of the Bajo tribe in Tinakin Laut Village, Banggai Laut Regency. In the past, the majority of them had low educational levels, necessitating awareness to encourage the Bajo community to value knowledge as much as possible. This research aims to understand the educational process for Bajo children in Tinakin Laut Village. The method employed in this study is a qualitative approach using ethnographic methods, involving data collection techniques such as observation, interviews, and documentation. The research data sources consist of primary and secondary data, with data analysis techniques including data reduction, data presentation, and drawing conclusions. The research results reveal several key findings. First, the education process in Tinakin Laut Village has undergone significant changes. In the past, the community there had little interest in education, but currently, the Bajo community has recognized the importance of education. Second, the education process in Tinakin Village is based on the willingness of children, parental encouragement and awareness, school support, and the influence of the surrounding environment. Third, the economic conditions in Tinakin Laut Village have improved, especially marked by increased job opportunities. Bajo parents in Tinakin Laut Village, who previously relied solely on sea resources, now consider job diversification to avoid dependence on seasons, enabling them to experience a prosperous life similar to the local Banggai community